Ketahanan Nonspesifik Ikan Mas (Cyprinus Carpio) Yang Direndam Ekstrak Daun Jeruju (Acanthus ilicifolius) Terhadap Infeksi Bakteri Aeromonas hydrophila - Dianti, Lusi; Prayitno, Slamet Budi; Ariyati, Restiana Wisnu (Journal of Aquaculture Management and Technology, 2013)
This research was aimed to study the clinical symptoms of fish infected by Aeromonas hydrophila and examine the effect of leaf extract Acanthus ilicifolius usage through the method of soaking to prevent Motile Aeromonas Septicemia disease. 96 fish was soaked with leaf of extract A. ilicifolius for 30 minutes. The challenge was done by injecting of bacterial suspensions Aeromonas hydrophila with 108 CFU/ml density intra-muscularly to the fish. The results showed clinical symptoms of moribund fish such as moving slowly, swimming on the surface, swim upsided, expothalmia, ulcer and accumulation of fluid in the abdominal cavity. Further results showed that extract of A. ilicifolius leaf did not significantly protected (P>0.05) the survival of tested fish. Observations of blood profile after infection showed the average from the highest to lowest total erythrocytes were C (500 ppm) of 2.69 x 106 cells/mm3, B (300 ppm) 2.31 x 106 cells/mm3, A (0 ppm) 2.29 x 106 cells/mm3 and D (700 ppm) 2.18 x 106 cells/mm3 recpectively. The average of the total leukocytes from the highest to lowest D (700 ppm) of 3.63 x 104 cells/mm3, C (500 ppm) 3.60 x 104 cells/mm3, B (300 ppm) 3.53 x 104 cells/mm3 and A (0 ppm) 3.47 x 104 cells/mm3 recpectively. The average value of the levels of highest to lowest hematokrit C (500 ppm) of 22.53%, D (700 ppm) 21,33% B (300 ppm) 20,67% and A (0 ppm) 20.33% recpectively. Leaf extract A. ilicifolius with dosage up to 700 ppm had not been able to improve imunne respone against infections of A. hydrophila